IMPLEMENTASI PROGRAM LAYANAN SEHARI SELESAI (LARI SAY) PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BANJARBARU - Sitna Hajar Malawat; Evy Emy Liantie (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2019)
The purpose of the study was to find out the description of how the implementation and the factors that influence the Completion of a Day Service Program (LARI SAY) at the Banjarbaru City Population and Civil Registration Service. The research method used a qualitative approach with descriptive type. Collection by interview and observation, to 5 (five) informants. Informants were determined using descriptive techniques. Data analysis using interactive models according to Miles & Huberman.The results of the study showed the Implementation of a One-Day Service Program (LARI SAY) at the Banjarbaru City Population and Civil Registration Service, viewed from Communication Indicators, Resource Indicators, Bureaucratic Structural Indicators, which were considered not optimal because they were still being repaired and improved while the Disposition Indicator was running optimally because in matters of disposition signing a service document a day is finished always done according to the procedure and time. The factors that affect consist of 2 (two) namely supporting factors and inhibiting factors. Supporting factors are a. Human Resources (HR); b. Disposition; and c. facilities and infrastructure while the inhibiting factor is a. network system; b. communication; and c. human behavior.